Integrating Conflict Resolution into Problem-Based Learning: A Novel Model to Enhance Social Skills in Early Childhood Education - Utami, Dian Tri; ., Hapidin; Supena, Asep (Journal of Cultural Analysis and Social Change, 2025)
This study develops and tests a Problem-Based Learning (PBL) model integrated with conflict resolution content to enhance social skills in early childhood education. Grounded in constructivist learning theory and the socio-emotional development framework, this research addresses the gap in early childhood pedagogy, where social competence is often underemphasized compared to cognitive domains. Using a Research and Development (R&D) design with both qualitative and quantitative approaches, the model was implemented in several early childhood institutions in Pekanbaru, Indonesia. The findings demonstrate that children who participated in the PBL model with embedded conflict resolution activities showed significant improvements in five key dimensions of social skills: communication, cooperation, responsibility, self-control, and social awareness. The study contributes a novel pedagogical framework that not only strengthens early social competencies but also aligns with 21st-century learning objectives emphasizing collaboration, empathy, and problem-solving.